The Kokel of Southern Siberia: New data on a post-Xiongnu material culture - Sadykov, Timur; Caspari, Gino; Blochin, Jegor; Lösch, Sandra; Kapinus, Yulija; Milella, Marco (PLOS ONE, 2021)
From the end of the Xiongnu Empire to the establishment of the first Turkic Khaganate, the territory of Southern Siberia sees the emergence of distinctive local material cultures. The Kokel culture is essentially unknown in the international English-language literature even though archaeological sites pertaining to this material culture are among the most common in Tuva (Southern Siberia). This makes them important for the understanding aspects of the sociocultural dynamics following the collapse of the first “steppe empire”. Here we present the results of the study of a Kokel funerary site recently excavated near the Early Iron Age kurgan Tunnug 1 and discuss the data in the context of the available Soviet and Russian literature. The Kokel culture substantially differs from the material culture of the Xiongnu and has to be seen as a largely independent cultural entity of small tribal groups without a pronounced social hierarchy engaging in frequent violent local conflict.